Prevalence of Hepatitis G Virus Among Hemodialysis and Kidney Transplant Patients in Khuzestan Province, Iran - Samarbaf-Zadeh, Ali Reza (Jundishapur J Microbiol, 2015)
BACKGROUND: Hepatitis G virus (HGV) is a member of Flaviviridae. Prevalence of HGV in healthy people is very low, but this virus is more prevalent in patients with hepatitis. Besides, relative frequency of HGV in patients undergoing hemodialysis, and kidney recipients is very high. The role of HGV in pathogenesis is not clear. Since this virus cannot be cultivated, molecular techniques such as Revers Transcription Polymerase Chain Reaction (RT-PCR) is applied to detect HGV. OBJECTIVES: The current study aimed to investigate the prevalence of HGV using determination of E2, viral envelope antigen, antibodies and the RNA by Enzyme Linked Immunosorbent Assay (ELISA) and RT-PCR techniques. The rational of the study was to determine the prevalence of HGV in patients undergoing hemodialysis and kidney transplantation in Khuzestan province, Iran. PATIENTS AND METHODS: Five hundred and sixteen serum samples of the patients undergoing hemodialysis and kidney transplantation from various cities of Khuzestan province were collected. Anti-hepatitis G E2 antibodies were investigated by ELISA method. RNAs were extracted from serums and Hepatitis G RNA was detected by RT-PCR. RESULTS: Of the 516 samples, 38 (7.36%) specimens were positive for anti-HGV by ELISA. All of these ELISA positive samples were negative for HGV genome by RT-PCR. Of the remaining 478 ELISA negative samples, 16 (3.14%) samples were positive by RT-PCR. CONCLUSIONS: Hepatitis G Virus was not prevalent in the patients undergoing hemodialysis and kidney transplantation in Khuzestan province. Although reports indicated high frequency of co-infection of HGV with hepatitis B and C viruses, in the current research, co-infection of HGV with B and C was not considerable. Since different groups and subtypes of HGV are reported, periodic epidemiologic evaluation of HGV and its co-infection with other hepatitis viruses is suggested in other populations such as the patients with thalassemia; however, periodic epidemiologic monitoring of HGV may be helpful to control future potential variations of the virus.